Investigation of (p,xd) reaction on 120Sn nucleus at proton energy of 30 MeV - Kerimkulov, Zh.K.; Alieva, G.Zh.; Mukan, Zh.; Alimov, D.K.; Khodzhayev, R. (Recent Contributions to Physics, 2021)
For the first time, the double-differential and integral cross-sections of the reaction (p,xd) on the 120Sn nucleus were measured at the energy of the bombarding protons of 30 MeV. Tin is the structural material of the nuclear power plants being designed, in particular, the promising ADS (Accelerator Driven System) hybrid electro-nuclear installations consisting of a high-energy proton accelerator and a deeply subcritical nuclear reactor. The main idea is to use high-energy charged particle accelerators to produce neutrons in heavy element targets. For registration and identification of reaction products, the dE-E method was used, where two parameters of the detected particle are registered: specific ionization and total energy. The total error of the measured double-differential cross sections did not exceed 20%. After integrating the double-differential cross sections by angle, the integral energy spectrum was determined. The theoretical analysis is carried out within the framework of the TALYS calculation code, which is based on modern theoretical models of nuclear decay. The mechanisms of nuclear reactions responsible for the formation of the energy spectrum of outgoing deuterons are determined. The obtained experimental results fill in the missing values of the cross-sections of the studied reactions and can be used in the development of new approaches to the theory of nuclear reactions, as well as in the design of hybrid nuclear power plants.